APE Islami Sebagai Media Interaktif di RA Ianatush Shibyan Batealit Jepara - Khalimatus Sa'diyah; Eko Darmawanto; Zainul Arifin Muhammad Abduh; Ari Purnomo Endah Aflahani (Universitas Islam Nahdlatul Ulama Jepara, 2017)
AbstractThis community Service aims to: 1) improve innovation and teachers? creativity to create a conventional Islamic Educative Game?s Tool (APE) as interactive media learning; 2) improve understanding of the partners of creative Islamic APE 3) improve the ability of teachers in making conventional Islamic APE as interactive media learning. The expected results are: 1) increase the creativity of teachers in an effort to support learning activities; 2) the partner has the capability of conventional Islamic APE planning as an interactive medium of learning; 3) increasing the ability of partners in the learning process; 4) the Islamic APE favored by student; and 5) be able to increase lecturer?s participation in community development activities. Both in the handling aspects of the creation, quality, diversity and production, always involves the participation of partners. The partners also involved in all phase of this service. So that the product as the result are Iqro? Puppet, Iqro' Puzzle, and other creative products by teachers of RA I'anatush Shibyan.Keywords: RA, Islamic APE, educational toy, empowerment, and Interactive MediaAbstrakTujuan kegiatan untuk : 1) meningkatkan keatifitas dan inovasi guru membuat APE Islami konvensional sebagai media interaktif pembelajaran; 2) meningkatkan pemahaman mitra tentang APE Islami yang kreatif 3) meningkatkan kemampuan guru dalam teknik pembuatan APE Islami konvensional sebagai media interaktif pembelajaran. Hasil dari kegiatan ini diantaranya : 1) meningkatkan kreatifitas guru sebagai upaya menunjang kegiatan pembelajaran; 2) mitra memiliki kemampuan perencanaan APE Islami konvensional sebagai media interaktif pembelajaran; 3) meningkatnya kemampuan mitra dalam melakukan proses pembelajaran; 4) kreasi APE Islami yang disukai anak didik; serta 5) mampu meningkatkan partisipasi dosen dalam kegiatan pemberdayaan masyarakat. Produk APE Islami konvensional berupa Wayang Iqro?, Puzzel Iqro? dan hasil kreasi guru-guru RA I?anatush ShibyanKata Kunci: APE Islami, RA, Pemberdayaan, Media interaktif